Acne vulgaris and treatment with topical retinoids - adapalene and tretinoin - Antos, Maria; Wawryszuk, Angelika; Bator, Piotr; Łyko, Grzegorz; Rachwał, Krystian; Bobrzyk, Adrian; Makowska, Weronika; Kamińska, Weronika; Kosel, Alicja; Rumian, Maciej (Journal of Education, Health and Sport, 2023)
Introduction and purpose: Acne vulgaris is a disease that mainly affects young people and is associated with overactive sebaceous glands. The disease mainly affects the face but can also occur on the back. Depending on the clinical picture, we can distinguish different types of acne and make our treatment dependent on it. The aim of the study will be to compare the effects of topical retinoids on acne vulgaris. State of knowledge: Topical retinoids have a direct anti-inflammatory effect and prevent the formation of blackheads and microcomedones. Five retinoids are currently available for topical treatment of acne vulgaris. We distinguish three generations. The mechanism of action is not fully understood, but it is known that they react with the RAR and RXR receptors. In the review paper, we will compare the effects of adapalene with tretinoin. Conclusion: According to the indicated study results, there is no significant difference in the effect of treatment with adapalene or tretinoin. Adapalene showed less irritation during treatment than tretinoin. The most important thing during acne treatment is choosing the right concentration and formulation by the dermatologist so that the patient does not stop treatment.